Fish Scale Collagen Peptides Protect against CoCl2/TNF-α-Induced Cytotoxicity and Inflammation via Inhibition of ROS, MAPK, and NF-κB Pathways in HaCaT Cells. (22nd June 2017) - Subhan, Fazli; Kang, Hae Yeong; Lim, Yeseon; Ikram, Muhammad; Baek, Sun-Yong; Jin, Songwan; Jeong, Young Hun; Kwak, Jong Young; Yoon, Sik
Abstract : Skin diseases associated with inflammation or oxidative stress represent the most common problem in dermatology. The present study demonstrates that fish scale collagen peptides (FSCP) protect against CoCl2 -induced cytotoxicity and TNF- α -induced inflammatory responses in human HaCaT keratinocyte cells. Our study is the first to report that FSCP increase cell viability and ameliorate oxidative injury in HaCaT cells through mechanisms mediated by the downregulation of key proinflammatory cytokines, namely, TNF- α, IL-1 β, IL-8, and iNOS. FSCP also prevent cell apoptosis by repressing Bax expression, caspase-3 activity, and cytochrome c release and by upregulating Bcl-2 protein levels in CoCl2 - or TNF- α -stimulated HaCaT cells. In addition, the inhibitory effects of FSCP on cytotoxicity and the induction of proinflammatory cytokine expression were found to be associated with suppression of the ROS, MAPK (p38/MAPK, ERK, and JNK), and NF- κ B signaling pathways. Taken together, our data suggest that FSCP are useful as immunomodulatory agents in inflammatory or immune-mediated skin diseases. Furthermore, our results provide new insights into the potential therapeutic use of FSCP in the prevention and treatment of various oxidative- or inflammatory stress-related inflammation and injuries.